KONTRIBUSI KEGIATAN EKSTRAKURIKULER KARATE DALAM PEMBENTUKAN KARAKTER DSIPLIN DAN TANGGUNG JAWAB PESERTA DIDIK DI MADRASAH IBTIDAIYAH - Hesti Nurul Isnaeni (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2019)
This study aims to observe the contribution of karate extrauricular activities to building the character of discipline and responsibility of students in MI Darul Hikmah Bantarsoka, West Purwokerto District, Banyumas Regency. This research is a field research, with a type of qualitative research. Data collection techniques use observation, interviews, and documentation. The data obtained from the three data collection techniques are then collected through triangulation of techniques and sources. From the results of the analysis conducted by researchers, karate extracurricular activities has positive contribution to building the character of discipline and responsibility in MI Darul Hikmah Bantarsoka, West Purwokerto District, Banyumas Regency. Students who take part in karate extracurricular activities have the character of discipline and responsibility. The disciplinary attitude of students can be seen through several activities such as: religious discipline, time discipline, discipline towards regulations, discipline of learning, and discipline in attitude. The character of the responsibilities of the students includes the responsibility of being exposed to the densiri, family, community, nation and state and God Almighty.